Cultural stress in the age of mass xenophobia: Perspectives from Latin/o adolescents. (January 2021) - Vos, Saskia R.; Shrader, Cho Hee; Alvarez, Vanessa C.; Meca, Alan; Unger, Jennifer B.; Brown, Eric C.; Zeledon, Ingrid; Soto, Daniel; Schwartz, Seth J.
Abstract: During the last four years, xenophobic rhetoric directed toward Latino immigrants in U.S. media outlets and political forums has greatly increased. Using a general inductive approach, this qualitative study examined the forms of cultural stress, with a focus on discrimination and xenophobia, experienced by Latino adolescents in urban U.S. settings in 2018 and 2019. Six focus groups were conducted in Miami and Los Angeles (three groups per city) with first- and second-generation tenth-grade Latino students (n = 34). The following four themes emerged from the data: perceived discrimination from other Latino subgroups (in-group discrimination), perceived discrimination from non-Latino groups (out-group discrimination), internalization of stressors and discrimination experienced by participants' parents, and the current U.S. political rhetoric surrounding immigration. Understanding cultural stress among Latino adolescents provides valuable insight for future interventions to offset negative health outcomes associated with cultural stress.